Are Bottom-Up Approaches in Development More Effective than Top-Down Approaches? - Md Shahidulla Kaiser (Journal of Asian Social Science Research, 2020)
This article analyzes both the top-down and bottom-up approaches of development interventions in the Global South with reference to historical backgrounds and particular case studies. It is a fact that channeling Western financial aid by using the top-down approach has not been successful when compared to the results of poverty reduction programs in poor Southern countries over the past decades. As a result, bottom-up institutions like NGOs and bottom-up development programs like microfinance emerged in the late 80s and have become popular across developing countries. However, recently, the performance of NGOs has been questioned and it is perceived that they have lost their roots. Moreover, the bottom-up NGOs seem unable to flourish further without financial aids although bottom-up development approaches seem to be more effective than top-down development approaches as they ensure people’s participation and right to choose. Hence, this article argues that no single development approach is more effective than another. In the globalized world, there are no scopes to justify isolation from each other since countries in the Global South still approach South-South Cooperation and also receive financial aid from the Northern donors. Although there are some gross failures of past top-down development approaches, then, not all the bottom-up approaches are fully successful. This article maintains that to ensure cohesive development works, the global world needs both development approaches.